Global research trends in radiotherapy for bone metastases: a systematic bibliometric analysis - Yin, Fadong; Liu, Xuan; Nan, Xianxiu; Zheng, Xianbin; Shi, Xinjue; Yuan, Jing; Qiteng, Liu; Gao, Yuyan (Frontiers in Oncology, 2025)
BackgroundWith the development of various advanced radiotherapy techniques, research related to radiotherapy for bone metastases has made great progress, and scholars have published a large number of publications. In this study, we summarized the knowledge structure of radiotherapy for bone metastases and outlined the research hotspots through bibliometric analysis.MethodsPublications on radiotherapy for bone metastases from 1992 to 2024 were searched in the Web of Science Core Collection (WoSCC) database. Countries, institutions, authors, references, and keywords in the field were visualized using VOSviewer version 1.6.19 and CiteSpace version 6.3.R1.Results1303 publications from 71 countries were included in this study. The number of research publications on radiotherapy for bone metastases has been increasing year by year. The United States of America (USA) ranking first in terms of publication count and co-citation frequency. The most prolific institutions and authors were the University of Toronto and Sahgal A, while Chow E was the most co-cited author. The most co-cited paper was published by Lutz S et al. in 2011 in Internation Journal Of Radiation Oncology Physics. “stereotactic body radiotherapy”, “spine metastases”, “spinal cord compression”, “ immunotherapy” and “oligometastases” are the main keywords of the current research topics.ConclusionsThe application of stereotactic body radiotherapy (SBRT) in the treatment of patients with bone metastases, especially oligometastases, has attracted extensive attention from researchers. How to choose reasonable radiotherapy for patients with complicated bone metastases has now become a research hotspot. Radiotherapy combined with immunotherapy may be the future development trend.